TANTANGAN GURU DALAM PENYELENGGARAAN PEMBELAJARAN DI ERA INDUSTRI 4.0 DAN SOCIETY 5.0 - Renny Husniati; Iwan Kresna Setiadi; Dewi Cahyani Pangestuti; Siwi Nugraheni (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Online learning is a substitute for face-to-face learning, because during the COVID-19 pandemic learning cannot be done face-to-face. Many teachers have difficulty, how to deliver online learning via an android phone or laptop. There are still many teachers who are ignorant and passive, always asking to be understood of all their shortcomings, find it difficult to divide their time and sometimes do not want to learn and do not want to adapt to the times. If the quality of some teachers is like that, when entering the 21st century can they still realize superior Indonesian human resources? This community service activity method uses the lecture method, provides examples through discussion, and questions and answers. The lecture method is used to convey general knowledge about the challenges of teachers in the 21st century. Questions and answers are used to complete things that have not been accommodated by the two methods above. This counseling involves lecturers from the Faculty of Economics and Business, in partnership with the District Education Office. Bogor which involves junior high school teachers. This program aims to (1) increase teacher knowledge and insight about the competencies that teachers must have in the industrial era 4.O and society 5.O, and (2) provide knowledge of what attitude choices teachers should have in facing the 21st century. Target The outputs of this service program are (1) Teachers as the frontline in preparing superior human resources, are always required to be consciously prepared to be willing to improve their competence, innovation, and creativity in learning. (2) Teachers must change their way of thinking, from thinking from routine work to lateral and constructive thinking for the sake of their students.